A dictionary of geology and earth sciences - Allaby, Michael (Oxford University Press, 2013)
Provides "concise entries on all aspects of geology and earth sciences, including planetary science, volcanology, palaeontology, and mineralogy."--Title screen
Previous editions published as: A dictionary of earth sciences.
Title from title screen (viewed October 11, 2013).
Keywords: Geology -- Dictionaries.; Earth sciences -- Dictionaries.; elektronické knihy; electronic books